2021
DOI: 10.26855/ijfsa.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

During Fermentation, Microbiology and Biochemistry of the Cocoa Bean

Abstract: The purpose of this research is to quantitatively and qualitatively examine the fermentation parameters of dry cocoa beans to be more effective in determining the role and function of microorganisms. The three fermentation methods are as follows: control (without inoculums), Saccharomyces cerevisiae (FNCC inoculums 3056), Lactobacillus lactis (FNC 0086), and Acetobacter aceti (FNCC 0016), all at a concentration of approximately 108 CFU/g were added simultaneously at the start of the fermentation (A), and all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…2), showing the coexistence of the embryo in the presence of external acidic conditions as a result of the conversion of sugars present in the pulp to ethanol and secondary products such as organic acids, aldehydes, and fatty acid esters by the prevalent yeast consortium. These concentration conditions of acetic acid, ethanol, and heat contribute to the death of the embryo 55‐57 . The drop in pH and rise in the percentage of total acidity inside the grain from day 2 onwards allows the permeability of the grain to be identified, giving rise to the migration of compounds from the seed testa to the cotyledon because of the conversion of ethanol to acetic acid, 9,56 with such behavior being present in all of the treatments investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…2), showing the coexistence of the embryo in the presence of external acidic conditions as a result of the conversion of sugars present in the pulp to ethanol and secondary products such as organic acids, aldehydes, and fatty acid esters by the prevalent yeast consortium. These concentration conditions of acetic acid, ethanol, and heat contribute to the death of the embryo 55‐57 . The drop in pH and rise in the percentage of total acidity inside the grain from day 2 onwards allows the permeability of the grain to be identified, giving rise to the migration of compounds from the seed testa to the cotyledon because of the conversion of ethanol to acetic acid, 9,56 with such behavior being present in all of the treatments investigated.…”
Section: Discussionmentioning
confidence: 95%
“…These concentration conditions of acetic acid, ethanol, and heat contribute to the death of the embryo. 55-57 57 The drop in pH and rise in the percentage of total acidity inside the grain from day 2 onwards allows the permeability of the grain to be identified, giving rise to the migration of compounds from the seed testa to the cotyledon because of the conversion of ethanol to acetic acid, 9,56 with such behavior being present in all of the treatments investigated. Different studies 9,13,58 have reported that the optimal pH for the development of aroma precursors at the end of the fermentation phase is between 5.0 and 5.5 because, in this pH range, the enzymes aspartateendoproteases and carboxypeptidases act jointly and the polypeptides, corresponding to subunits of 7S globulins or vicilins, 13,59 are degraded selectively.…”
Section: Discussionmentioning
confidence: 99%
“…Food utilization is comprised of five components, the first of which is access to clean water and the second of which is access to health facilities more than 5 kilometers away [33], [35]- [38]. In everyday life, clean water is a very important necessity for most households [39]- [41].…”
Section: Food Utilizationmentioning
confidence: 99%
“…This attitude towards the conduct of farmers reveals that the vast majority of farmers have a very strong aim for behaviour connected to developing the environmentally sustainable business of oil palm farms. [11] Ecological awareness is motivated to preserve the environment through individual intentions and behaviours [12]. Farmers benefit economically, socially, and psychologically from participating in farmer groups to increase competitiveness and sustainability [13].…”
Section: Behavioural Intentions Of Independent Palm Oil Smallholders ...mentioning
confidence: 99%